2022
DOI: 10.1186/s12886-022-02356-4
|View full text |Cite
|
Sign up to set email alerts
|

Thickness measurements taken with the spectralis OCT increase with decreasing signal strength

Abstract: Background Optical coherence tomography (OCT) is used worldwide by clinicians to evaluate macular and retinal nerve fiber layer (RNFL) characteristics. It is frequently utilized to assess disease severity, progression and efficacy of treatment, and therefore must be reliable and reproducible. Objective To examine the influence of signal strength on macular thickness parameters, macular volume measurement and RNFL thickness measured by spectral-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The quantitative results of this study revealed that there are no significant differences between the two A-scan rates OCT in the thickness measurements of the retinal layers. The 85 kHz A-scan rate OCT is a reliable and reproducible diagnostic tool in retinal imaging [ 16 , 17 , 18 ]. The 20 kHz A-scan rate OCT demonstrated a comparable reproducibility in terms of the accuracy of retinal layer segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative results of this study revealed that there are no significant differences between the two A-scan rates OCT in the thickness measurements of the retinal layers. The 85 kHz A-scan rate OCT is a reliable and reproducible diagnostic tool in retinal imaging [ 16 , 17 , 18 ]. The 20 kHz A-scan rate OCT demonstrated a comparable reproducibility in terms of the accuracy of retinal layer segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were age older than 50 years, presence of AMD diagnosis, and the presence of high-quality OCTA scans in the database (defined as lack of motion artifacts and background noise and quality index Q had to be > or = 25). 21,22 Of 400 initially chosen OCTA scans, we excluded 14 scans due to the diagnosis of CNV of the etiology different than AMD (9 myopic CNV, two CNV secondary to central serous chorioretinopathy, and three peripapillary CNV) and 76 scans were excluded due to motion artifacts, incomplete scan, background noise, and poor quality of the scan (defined with quality index Q < 25). Each eye was analyzed independently.…”
Section: Methodsmentioning
confidence: 99%
“…or = 25). 21,22 Of 400 initially chosen OCTA scans, we excluded 14 scans due to the diagnosis of CNV of the etiology different than AMD (9 myopic CNV, two CNV secondary to central serous chorioretinopathy, and three peripapillary CNV) and 76 scans were excluded due to motion artifacts, incomplete scan, background noise, and poor quality of the scan (defined with quality index Q , 25). Each eye was analyzed independently.…”
Section: Optical Coherence Tomography Angiography Data Selection and ...mentioning
confidence: 99%
“…The median Automatic Real Time (ART) function and signal index quality were exported for each of the included ring scans. Signal quality between 20 and 25 is considered good and above 25 excellent 14 …”
Section: Methodsmentioning
confidence: 99%
“…Signal quality between 20 and 25 is considered good and above 25 excellent. 14 We analyzed the superior temporal arteriole of the central retinal artery at its crossing on the 12 • circular scan using intensity-based analysis. Inner wall thickness (IWT), outer wall thickness (OWT), and LD were assessed in both eyes.…”
Section: Oct Examination and Assessment Of The Retinal Arteriolesmentioning
confidence: 99%